Careers What's Up, PostDoc?. - Patel-Predd, P. (IEEE spectrum)
This paper provides an insight into what electrical and computer engineering Ph.D. holders should expect if and when they decide to pursue an academic career. Typically, young academics in the US start out as assistant professors, become associate professors if they get tenure, and may then be promoted to full professors. However, there are institutions that have eliminated the tenure process and replaced it with a system based on the entrepreneurship principle, wherein faculty members are offered five-year contracts that are renewed based on their teaching and research performance. Nevertheless, many still believe in the tenure process, saying that it drives the bar up for quality. The job security that comes with tenure gives academics freedom to voice their opinions and to perform high-risk, high-reward research as well as teaching